A Study of Antibiotics Self-Medication at Primary Health Care Centers in Shiraz, Southern Iran - Mehrdad Askarian; Mohsen Hosseingholizadeh mahani; Mina Danaei; Mohsen Momeni (Shiraz University of Medical Sciences, 2013)
Background: Nowadays, self-medication of therapeutic agents is of global concern particularly in developing and underdeveloped countries. Some studies conducted in Iran showed that the frequency of self-medication was significant. Objective: This research was conducted to estimate the prevalence of arbitrary use of antibiotics in Shiraz community with special interest in its determinant factors. Methods: This cross-sectional study was conducted in Shiraz, in 2009. Approximately 710 out of all patients referred to all health care centers in Shiraz were selected to fill out a questionnaire containing 23 questions divided into two parts. The frequency of self-medication according to demographic factors was described and the association between independent variables and selfmedication was analyzed. Results: The frequency of self-medication in this study was 44.5% and the request to prescribe antibiotics by the patients was 53.5%. Amoxicillin was the most widely used drug by the participants. There was a significant association between age and gender with self-medication. The frequent cause for self-medication was common cold. Approximately, 74.4% of the participants reported their previous experience as the main reason for self-medication. Conclusion: The results of this survey demonstrated the high frequency of self-medication in Shiraz. Socio-cultural determinants are the etiologic factors for self-medication. Policy makers are recommended to provide community-wide educational programs to make people aware about the adverse effects of self-medication. There was a significant association between age, gender and education with self-medication and governments could pay more attention to these factors for designing the interventional programs.